Differentiated short- and long-term impacts of a starter stimbiotic supplementation on gut health in broilers fed wheat and rye-based diets at homeostasis and under Eimeria tenella challenge - Vincent Jonchère; Françoise I. Bussière; Olivier Zemb; Vahid Khaksar; Léa Cornaille; Eric Gambier; Flavie Derouin-Tochon; Fabien Hervo; Catherine Schouler; Xavière Rousseau; Mike Bedford; Sandrine V. Mignon; et al. (Animal Nutrition)
The postnatal period, covering roughly the first 10 days post–hatch, is critical for early development of the digestive tract in poultry. This period is characterized by high plasticity of the digestive tract, offering a unique window in which to shape digestive phenotypes toward improved nutrient absorption efficiency, enhanced gut health, and optimized microbiota composition. Feed additives, such as xylanase and xylo-oligosaccharides (XOSs), are known to modulate digestive physiology, especially the gut microbiota, which could, in turn, influence the outcome of infections within the gastrointestinal tract. The aim of this study was to assess the effects of a stimbiotic (STB; a combination of xylanase and XOSs) supplementation provided either during the starter, the grower, or during both periods in the context of an Eimeria tenella challenge, focusing on growth performance, ileal monomeric sugar residues, cecal metabolome and microbiota composition. From 0 to 23 d, a total of 192 chicks were assigned to 8 different treatments in a 2 × 2 × 2 factorial design. Two levels of stimbiotic (0 or 100 g/t), two periods of supplementation (starter or grower) and two challenge statuses (unchallenged or E. tenella challenged at d 16) were tested. During the starter period, STB supplementation tended to enhance average daily gain (P = 0.052) and significantly reduced the abundance of two Lachnospiraceae genera (P < 0.001; P = 0.030), accompanied by decreased concentrations of two short-chain fatty acids (SCFAs) in the caecal content (P = 0.029; P = 0.015) at d 9. In the ileum, STB supplementation reduced the concentration and proportion of soluble sugars (P = 0.006). By the end of the grower period at d 23, starter STB supplementation resulted in increased abundance of two genera within the family Lachnospiraceae (Lachnospiraceae ruminococcus, P = 0.043; Lachnospiraceae anaerostipes, P = 0.013) and elevated production of butyrate and acetate (P = 0.042; P < 0.001). Under E. tenella challenge, during the grouper period, STB supplementation maintained growth performance at levels comparable to unchallenged chickens (P = 0.027). In conclusion, STB supplementation influences microbial composition and fermentation, with lasting effects resulting from post–hatch feeding. These findings support the use of STB to improve the resilience of chickens under pathogenic challenges.